Online Support Model For Successful Exclusive Breastfeeding - Eka Riyanti; Diah Astutiningrum; Herniyatun Herniyatun (Universitas STRADA Indonesia, 2020)
Breastfeeding support is an important factor in ensuring the mother can overcome the challenges of breastfeeding. Social media use can also influence breastfeeding attitudes, breastfeeding norms and increase self-efficacy. But what kind of online support is not clear which model is used.The purpose of this study was to identify the effectiveness of online support for the success of exclusive breastfeeding. This study used an experimental design, namely Quasi-experimental post test with control design. The sample in this study were mothers with infants 2-5 months who met the criteria. The success of exclusive breastfeeding was measured using the Breastfeeding self-efficacy scale (BSES) instrument and the Bristol Breastfeeding Assessment Tool (BBAT).The results showed that the online support model intervention had an influence on self-efficacy in the intervention group (p = 0.009). Whereas the attachment variable has no effect (p = 0.082)